The centurion's wife - Bunn, T. Davis, 1952- (Bunn, T. Davis, 1952- Acts of faith, 2009)
Leah, a young Jewess of mixed heritage, is secretly commissioned to discover the truth behind the death of an obscure rabbi in the Roman backwater of first-century Palestine while also being engulfed in her own turmoil--facing the prospect of an arranged marriage to a Roman soldier, Alban, who seems to care for nothing but his own ambitions as leader of the Roman garrison near Galilee.